An Analysis of Code Mixing Used by Major Characters of Layangan Putus Tv Series - Yeni Mutmainnah; Merry Rullyanti; Dhanu Ario Putra (Literary Criticism, 2022)
Abstract Nowadays, the use of code mixing is easily found in the oralcommunication, especially in the daily communication amongteenagers who like to code and switch their language to show thatthey are modern. The objectives of this research are to find out typesof code mixing used by major characters of Layangan Putus tv seriesand to know the factors that cause the use of code mixing. This studyemployed a qualitative descriptive method as research design.Layangan Putus Tv Series was chosen as the object of this study. Inthis case, the researcher took the utterance from major characters(Kinan, Aris, and Lidya) in 10 episodes of the film as the source ofthe data of this research. The instrument used in this research wasobservation checklist. The checklist consisted of the types of codemixing based on Muysken (2000) theory. There were two findings ofthis research; First, there were three types of Code Mixing used bymajor characters of Layangan Putus TV Series. There were 113insertion, 108 alternation, and 9 congruent lexicalization. Second,there were maybe four factors cause the use of code mixing inLayangan Putus TV series, namely; the participants, the setting orsocial context of interaction, the topic, and the function ofconversation. As a consequence, the researcher recommends thatfuture researchers should make a study of the phenomenon of codemixingin the latest and best TV series and Movie produced byDirector from Indonesia. Key Words: Code Mixing, Layangan Putus TV Series, MajorCharacters